2023
DOI: 10.6004/jnccn.2023.0006
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Neoplasms, Version 1.2023, NCCN Clinical Practice Guidelines in Oncology

Abstract: Adenocarcinoma of the endometrium (also known as endometrial cancer, or more broadly as uterine cancer or carcinoma of the uterine corpus) is the most common malignancy of the female genital tract in the United States. It is estimated that 65,950 new uterine cancer cases will have occurred in 2022, with 12,550 deaths resulting from the disease. Endometrial carcinoma includes pure endometrioid cancer and carcinomas with high-risk endometrial histology (including uterine serous carcinoma, clear cell carcinoma, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
110
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(167 citation statements)
references
References 304 publications
0
110
0
1
Order By: Relevance
“…Sentinel node mapping has been adopted and accepted worldwide for nodal evaluation in women with low-grade endometrial cancer [ 12 ]. However, a recent review of the literature conducted by How et al [ 22 ], they reported that SLN biopsy generated similar detection rates and accuracy as seen in low-grade disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sentinel node mapping has been adopted and accepted worldwide for nodal evaluation in women with low-grade endometrial cancer [ 12 ]. However, a recent review of the literature conducted by How et al [ 22 ], they reported that SLN biopsy generated similar detection rates and accuracy as seen in low-grade disease.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several publications have shown that SLN mapping is an effective method for identifying disease in the lymph nodes, reporting high sensitivity, low false-negative rates, as well as good negative predictive values [ 9 , 10 , 11 ]. The most recent National Comprehensive Cancer Network (NCCN) and ESGO guidelines [ 12 , 13 ] support SLN mapping as part of the surgical staging of endometrial cancer, providing there is strict adherence to the principles and algorithm of the technique [ 14 ]. The surgical SLN algorithm has been proposed to reduce the false-negative rare in women with disease apparently confined to the uterine body.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, their clinical characteristics are not well known because the number of reported cases is too low. Generally, the treatment of choice of uterine leiomyosarcoma is total hysterectomy with or without bilateral salpingo-oophorectomy, and chemotherapy or external beam radiation therapy is optional [3]. In case of advanced stage, systemic chemotherapy can be considered, although postoperative treatment has not been established [4].…”
Section: Introductionmentioning
confidence: 99%
“…It is now understood that the histological classi cation of EC cannot fully meet the clinical needs for predicting prognosis and guiding precise treatment due to the high heterogeneity of EC tissues and traditional histopathological diagnosis with low repeatability. The molecular classi cation ("TCGA classi cation") of EC was recently recommended by the National Comprehensive Cancer Network (NCCN) guidelines [21], which could assist prognosis evaluation, provide new strategies for individualized treatment, and bene t the prediction of immunotherapy. It has been established that HGOSC has an indolent response to platinum-and taxolbased chemotherapy [1].…”
Section: Introductionmentioning
confidence: 99%